2022
DOI: 10.1093/annweh/wxab113
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Asthma: The Knowledge Needs for a Better Management

Abstract: The management of occupational asthma (OA) may be influenced by several factors and removal from exposure is the main tertiary prevention approach, but it is not always feasible without personal and socioeconomic consequences. Reducing the delay between the onset of suggestive symptoms of OA and the diagnosis of OA is associated with a better prognosis. Workers’ education to increase awareness to trigger agents and a medical surveillance program directed especially at at-risk workers could be helpful in reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…OA can also lead to significant negative socioeconomic impacts [1 ▪▪ ,36]. Roio et al [33 ▪ ] showed that patients with WRA had an overall reduced income after their diagnosis compared to patients with nonwork-related asthma.…”
Section: Prognosismentioning
confidence: 99%
“…OA can also lead to significant negative socioeconomic impacts [1 ▪▪ ,36]. Roio et al [33 ▪ ] showed that patients with WRA had an overall reduced income after their diagnosis compared to patients with nonwork-related asthma.…”
Section: Prognosismentioning
confidence: 99%
“…Scientists have determined that various types of occupational hazards (dust, gases, smoke, vapors, and others) that can act in the workplace can cause the development of AR through immunological or irritating non-immunological mechanisms [2][3][4]. This position is supported by the working group of the European Academy of Allergy and Clinical Immunology, which pointed out the close interaction between the upper and lower respiratory tracts and proposed the appropriate classification of AR subphenotypes, which is similar to occupational asthma [5][6][7].…”
Section: Introductionmentioning
confidence: 99%